Pengaruh Literasi Keuangan Dan Digital Payment Terhadap Perilaku Konsumtif Dengan Pengendalian Diri Sebagai Variabel Pemoderasi - Saputra, Galang Rio Adi; Suyanto, Suyanto; Sari, Gustin Padwa (Universitas Muhammadiyah Metro, 2023)
This study aims to analyze financial literacy and digital payments on consumptive behavior with self-control as a moderating variable in students of the faculty of economics and business, University of Muhammadiyah Metro. The type of research used in this research is quantitative. This study used primary data through questionnaires and the population in this study totaled 1063 students. Then the sampling technique in this study used the slovin formula to determine the number of samples, namely 265 respondents. The results of this study indicate that Financial Literacy has an effect on Consumptive Behavior, Digital Payment has an effect on Consumptive Behavior, and Self-Control moderates Financial Literacy on Consumptive Behavior, and Self-Control does not moderate Digital Payment on Consumptive Behavior in students of the Faculty of Economics and Business Muhammadiyah Metro University.